Role of epigenetics in lung cancer heterogeneity and clinical implication. (April 2017) - Dong, Nian; Shi, Lin; Wang, Diane C.; Chen, Chengshui; Wang, Xiangdong
Abstract: Lung cancer, as a highly heterogeneous disease, can be initiated and progressed through the interaction between permanent genetic mutations and dynamic epigenetic alterations. However, the mediating mechanisms of epigenetics in cancer heterogeneity remain unclear. The evolution of cancer, the existence of cancer stem cells (CSCs) and the phenomenon of epithelial-mesenchymal transition (EMT) have been reported to be involved in lung cancer heterogeneity. In this review, we briefly recap the definition of heterogeneity and concept of epigenetics, highlight the potential roles and mechanisms of epigenetic regulation in heterogeneity of lung cancer, and summarize the diagnostic and therapeutic implications of epigenetic alterations in lung cancer, especially the role of DNA methylation and histone acetylation. Deep understanding of epigenetic regulation in cancer heterogeneity is instrumental to the design of novel therapeutic approaches that target lung cancer.